LEGAL PROTECTION OF CONSUMERS IN HOME ORDER LETTER (SPR) FROM THE DEVELOPER - Maria Francisca (Problematika Hukum, 2019)
The initial process of buying a house at a developer company is carried out with a House Order Letter (SPR) and the consumer is immediately given a receipt for the purchase of a house unit. In its implementation, this SPR uses standard clause agreements which are more detrimental to consumers. In the course of this credit agreement, preceded by an SPR from the developer company, it became a thing that was detrimental to the community who had paid the receipt and was canceled unilaterally by the developer company on the grounds that the bank refused to apply for a mortgage. In this case, legal protection is needed for consumers to get a full refund of what they deposited because the unilateral cancellation has been carried out by the Developer Company. Business actors as parties who make agreements use standard clauses that tend to release, transfer or reduce their responsibilities which should be the responsibility of business actors, by violating Article 18 paragraph (4) UUPK, so that in general, consumer rights are still not protected because business actors are concerned with the fulfillment of protection for their parties against the risks they may face. The SPR agreement does not conflict with applicable law but its moral responsibility is required to protect consumers.